2018
DOI: 10.4049/jimmunol.1800129
|View full text |Cite
|
Sign up to set email alerts
|

IFNAR1 Controls Autocrine Type I IFN Regulation of PD-L1 Expression in Myeloid-Derived Suppressor Cells

Abstract: Tumor cells respond to IFN-γ of activated T cells to upregulate programmed death-ligand 1 (PD-L1) in the tumor microenvironment as an adaptive immune resistance mechanism. Tumor cells also express oncogene-driven PD-L1. PD-L1 is also expressed on myeloid-derived suppressor cells (MDSCs). It is known that both type I and II IFNs upregulate PD-L1 expression in MDSCs. However, the molecular mechanism underlying PD-L1 expression in MDSCs is still largely unknown. We report in this article that MDSCs exhibit consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 49 publications
6
51
2
Order By: Relevance
“…Furthermore, substantial upregulation of programmed cell death receptor ligand 1 (PD‐LI), an important immune checkpoint inhibitor of T cell activation, was observed. Previous studies have shown that type I IFN triggers PD‐LI expression on APCs . Indeed, significantly higher levels of cytokines such as IFN‐α and TNF‐α were detected in co‐culture with SKBR3_rNDV than with SKBR3 (Fig.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Furthermore, substantial upregulation of programmed cell death receptor ligand 1 (PD‐LI), an important immune checkpoint inhibitor of T cell activation, was observed. Previous studies have shown that type I IFN triggers PD‐LI expression on APCs . Indeed, significantly higher levels of cytokines such as IFN‐α and TNF‐α were detected in co‐culture with SKBR3_rNDV than with SKBR3 (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…Previous studies have shown that type I IFN triggers PD-LI expression on APCs. 2,24 Indeed, significantly higher levels of cytokines such as IFN-α and TNF-α were detected in co-culture with SKBR3_rNDV than with SKBR3 ( Fig. 4b), no additional cytokine was detected as noted in the Table 1.…”
Section: Ndv-infected Tumor Cells Potentiate DC Maturationmentioning
confidence: 82%
“…The inhibition of the NF-κB pathway impairs the IFN-γ-mediated induction of PD-L1 expression [89], which is in line with the inhibition/downregulation of PD-L1 expression by inhibitors directed against NF-kB, JAK1/JAK2 and BTK [90]. In addition to IFN-γ, type I IFNs can also induce PD-L1 expression [91]. Other inflammatory stimuli affecting PD-L1 expression in tumors include lipopolysaccharide (LPS) by triggering TLR4, TNF-α and IL-4 and in DC, in particular IL-1β, IL-6, IL-27, IL-10 and TGF-β [13] (summarized by Sun et al, 2018).…”
Section: Transcriptional Regulation Of Pd-l1 Expression By Inflammatomentioning
confidence: 60%
“…If the process of the maturation of myeloid precursors was abrogated at different stages by some cytokines like TNF‐α, MDSCs will be generated eventually such pathological conditions as cancer (Fig. ) . The frequency of MDSCs was found to be closely associated with the progression and clinical staging in some cancer patients and tumor bearing mice.…”
Section: Introductionmentioning
confidence: 99%